2021
DOI: 10.20883/medical.e499
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of finisher files in the removal of calcium hydroxide paste from the root canal system – preliminary results

Abstract: Introduction. Successful endodontic treatment is affected by a number of factors associated with the disinfection and filling of the root canal. The chemical-mechanical root canal preparation consists in a thorough removal of any content from the pulp space, including inflamed pulp, bacteria, as well as canal filling materials. Aim. The aim of the study was to analyse the efficacy of the XP-endo Finisher and the Brush-Finisher on the removal of a calcium hydroxide dressing. Material and Methods. The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The results of the (PUI) group revealed no statistically significant difference in the value of Ca(OH) 2 remnants between segments; this part of the findings came in agreement with Gawdat & Elkhodary, 2017 [34] . The results of the Brush File group agreed with the study of Koprowicz & Koprowicz, 2021 [41] , which reported the use of the Gentlefile-Brush for improving Ca(OH) 2 removal. Regardless of technique, Ca(OH) 2 elimination was more efficient in "the coronal" and "middle thirds" of the canal than in the apical third.…”
Section: Discussionsupporting
confidence: 83%
“…The results of the (PUI) group revealed no statistically significant difference in the value of Ca(OH) 2 remnants between segments; this part of the findings came in agreement with Gawdat & Elkhodary, 2017 [34] . The results of the Brush File group agreed with the study of Koprowicz & Koprowicz, 2021 [41] , which reported the use of the Gentlefile-Brush for improving Ca(OH) 2 removal. Regardless of technique, Ca(OH) 2 elimination was more efficient in "the coronal" and "middle thirds" of the canal than in the apical third.…”
Section: Discussionsupporting
confidence: 83%
“…The third infection pathway is the anachoresis process—bacteria is supplied with blood and/or lymph through vessels into the apical region of a damaged root. Treatment of pulp disorders proceeds as follows: removing infected pulp structures, shaping root canals for filling, cleaning and decontamination and finally, restoration [ 73 , 74 ]. Among the many bacteria infecting root canals ( Actinomyces naeslundii , Aggregatibacter actinomycetemcomitans , and Fusobacterium nucleatum ), Enterococcus faecalis is the primary cause of dental pulp infections; as a facultative anaerobe, it can persist in unfavorable conditions, especially when it penetrates the dental tubules.…”
Section: Endodonticsmentioning
confidence: 99%